Dominant effect of the grain size of the MAPbI3 perovskite controlled by the surface roughness of TiO2 on the performance of perovskite solar cells - Nukunudompanich, Methawee; Budiutama, Gekko; Suzuki, Kazuma; Hasegawa, Kei; Ihara, Manabu (CrystEngComm, 2020)
Lead-halide perovskite solar cells (PSCs) have attracted attention due to their outstanding high power-conversion efficiency. In conventional inorganic solar cells such as Si solar cells, the relationship between cell performance and crystal grain size has been extensively discussed. However, in PSCs, the effect of the grain size on the cell performance has not previously been separated from other accompanying effects such as passivation at the grain boundary and variation in thickness and quality of the grains. Here, the average grain size of the methylammonium lead triiodide (MAPbI3) perovskite could be controlled alone by the surface roughness (Rms) of the compact TiO2 layer using the same preparation conditions used for MAPbI3. The direct dominant effect of the MAPbI3 grain size on the inorganic PSC performance could be observed by controlling alone the Rms of the compact TiO2 as an electron transport layer. For a PSC with an active area of 0.54 cm2, when the MAPbI3 grain size was increased from 150 nm to 350 nm, the current density, respectively, increased from 8 to 17 mA cm−2 and the photoelectric conversion efficiency from 6.1% to 11.4%. When a PSC with 0.54 cm2 active area size had a compact TiO2 layer that had a lower Rms of about 3 nm, the average MAPbI3 grain size was between 300 nm and 400 nm, and the resulting efficiency for a PSC was 11.4%, and that with 0.16 cm2 was 13.6%. When the MAPbI3 grain size was increased, the shunt resistance increased and the serial resistance decreased. The increased MAPbI3 grain size is clearly a crucial parameter to attain higher efficiency in PSCs.